Comparison between Golnar product and placebo in heavy menstrual bleeding: A double-blind randomized clinical trial - Fataneh Hashem-Dabaghian; Fatemeh Yousefi; Maryam Kashanian; Ismail Nazem; sodabeh bioos; Omod sadeghpour; Jaleh Aliasl (Mashhad University of Medical Sciences, 2020)
Objective: Golnar product is a poly herbal formulation advised by Persian medicine to control heavy menstrual bleeding (HMB). This study was conducted to compare the efficacy of this product with placebo in patients with HMB. Materials and Methods: In this double-blind randomized clinical trial, 100 women with HMB were randomly assigned into two groups. The patients in the Golnar group (n=50) took Golnar capsules 500 mg three times a day for the first 7 days of menstrual cycle for three cycles. The placebo group (n=50), took placebo capsules in the same manner. The duration and volume of bleeding (using Pictorial Blood Loss Assessment Chart: PBAC), quality of life (using Menorrhagia Questionnaire: MQ), and hemoglobin level (Hb) were measured 3 months after initiation of the intervention. Results: Eighty-two patients (43 in the Golnar and 39 in the placebo groups) completed the 3-month intervention period. In the Golnar group, PBAC score decreased from 201.62 (144.11) to 109.44 (69.57) (p<0.001) and MQ score improved significantly from 0.58 (0.27) to 0.39 (0.31) (p<0.001), while changes in placebo group were not significant. Hb increased in the Golnar group from 12.78±0.98 to 12.97±0.95 mg/dl (p=0.048) and decreased in the placebo group from 12.94±1.08 to 12.44±1.01mg/dl (p<0.001). No significant adverse effects were found in the Golnar group. Conclusion: The Golnar product can be considered an effective intervention for patients with HMB. Assessment of side-effects is suggested to be performed in a larger sample. In addition, a comparison between the Golnar product and nonsteroidal anti-inflammatory drugs could be valuable.